The Nutritional Profiles of Five Important Edible Insect Species From West Africa—An Analytical and Literature Synthesis - Anankware, Jacob P.; Roberts, Benjamin J.; Cheseto, Xavier; Osuga, Isaac; Savolainen, Vincent; Collins, C. M. (Frontiers in Nutrition, 2021)
Background: Undernutrition is a prevalent, serious, and growing concern, particularly in developing countries. Entomophagy - the human consumption of edible insects, is a historical and culturally established practice in many regions. Increasing consumption of nutritious insect meal is a possible combative strategy and can promote sustainable food security. However, the nutritional literature frequently lacks consensus, with interspecific differences in the nutrient content of edible insects generally being poorly resolved. Aims and methods: Here we present full proximate and fatty acid profiles for five edible insect species of socio-economic importance in West Africa: Hermetia illucens (black soldier fly), Musca domestica (house fly), Rhynchophorus phoenicis (African palm weevil), Cirina butyrospermi (shea tree caterpillar), and Macrotermes bellicosus (African termite). These original profiles, which can be used in future research, are combined with literature-derived proximate, fatty acid, and amino acid profiles to analyse interspecific differences in nutrient content. Results: Interspecific differences in ash (minerals), crude protein, and crude fat contents were substantial. Highest ash content was found in H.illucens and M.domestica ( 10% and 7.5% of dry matter respectively), highest crude protein was found in C.butyrospermi and M.domestica ( 60% of dry matter), whilst highest crude fat was found in R.phoenicis ( 55% of dry matter). The fatty acid profile of H.illucens was differentiated from the other four species, forming its own cluster in a principal component analysis characterised by high saturated fatty acid content. Cirina butyrospermi had by far the highest poly-unsaturated fatty acid content at around 35% of its total fatty acids, with α-linolenic acid particularly represented. Amino acid analyses revealed that all five species sufficiently met human essential amino acid requirements, although C.butyrospermi was slightly limited in leucine and methionine content. Discussion: The nutritional profiles of these five edible insect species compare favourably to beef and can meet human requirements, promoting entomophagy’s utility in combatting undernutrition. In particular, C.butyrospermi may provide a source of essential poly-unsaturated fatty acids, bringing many health benefits. This, along with its high protein content, indicates that this species is worthy of more attention in the nutritional literature, which has thus-far been lacking.